Role of Intravenous Dexmedetomidine for Attenuation of Hemodynamic Response to Laryngoscopy and Intubation in Controlled Hypertensive Patients: A Prospective Cohort Study: Intravenous Dexmedetomidine: Laryngoscopy and Intubation in Controlled Hypertensive Patients - Saeed, Areej; Abbas, Syed Muhammad; Abbas, Muhammad Qamar; Malik, Shakeel; Kumar, Vijai; Khurana, Sagar (Pakistan Journal of Health Sciences, 2026)
Due to sympathetic stimulation, laryngoscopy and endotracheal intubation are known to cause brief but noticeable elevations in blood pressure and heart rate, which can be dangerous for hypertensive individuals. It has been demonstrated that the specific α2-adrenergic agonist dexmedetomidine reduces these reactions. Objectives: To evaluate whether intravenous dexmedetomidine could effectively reduce hemodynamic reactions to laryngoscopy and intubation in patients with controlled hypertension. Methods: This prospective cohort study was carried out at Sindh Institute of Urology and Transplantation (SIUT) and used a non-probability consecutive sampling technique for six months from January 1, 2025, to June 30, 2025. Eligible were ASA II patients with high blood pressure who had been planned for elective surgery while under the influence of general anesthesia. Individuals were randomly assigned to receive either a placebo (20 mL normal saline) or dexmedetomidine (0.5 µg/kg diluted to 20 mL in saline) ten minutes before induction. Repeated-measures ANOVA and the Student’s t-test were used to examine the data; p ≤0.05 was deemed significant. Results: The groups’ baseline characteristics were similar. When compared to control, dexmedetomidine significantly reduced the increase in HR and SBP following laryngoscopy and intubation (p < 0.001 at all post-intubation intervals). Bradycardia (5.7%) and hypotension (2.9%) were rare but clinically treatable adverse effects. Conclusions: In hypertensive patients, intravenous dexmedetomidine (0.5 μg/kg) administered as a single pre-induction dosage is safe and efficient in reducing the hemodynamics of laryngoscopy and intubation while also enhancing cardiovascular stability throughout induction.